2013
DOI: 10.1111/ajo.12033
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy in women who underwent hysterectomy for uterine prolapse

Abstract: The risk of missing an uterine malignancy in patients with uterine prolapse is low if appropriate investigations are carried out prior to surgery. If hysterectomy is to be performed, we recommend that all surgical specimens be subjected to histopathological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…9 Wan OY et al reported the risk of CIN as 0.78% in his study, the majority of women in the study by Duhan et al were in the fourth to sixth decade of life, multiparous, and with symptoms of prolapse. 10,11 Although 88.28% of cervices revealed chronic cervicitis, 5 cases (1.36%) had evidence of invasive cervical malignancy on histology. Cuzick et al found one case (0.3%) of cervical cancer in a 71-year-old patient who had negative smear tests 14 months before surgery and one case (0.3%) of CIN-3 in a 66-year-old patient with normal smear test results 3 years before surgery and 3 cases of CIN-1 with normal smear tests 6 months to 3 years before surgery.…”
Section: Figure 4: Post-operative Specimen (Posteriorly)mentioning
confidence: 99%
“…9 Wan OY et al reported the risk of CIN as 0.78% in his study, the majority of women in the study by Duhan et al were in the fourth to sixth decade of life, multiparous, and with symptoms of prolapse. 10,11 Although 88.28% of cervices revealed chronic cervicitis, 5 cases (1.36%) had evidence of invasive cervical malignancy on histology. Cuzick et al found one case (0.3%) of cervical cancer in a 71-year-old patient who had negative smear tests 14 months before surgery and one case (0.3%) of CIN-3 in a 66-year-old patient with normal smear test results 3 years before surgery and 3 cases of CIN-1 with normal smear tests 6 months to 3 years before surgery.…”
Section: Figure 4: Post-operative Specimen (Posteriorly)mentioning
confidence: 99%
“…The risk of an asymptomatic woman being diagnosed with coincidental endometrial carcinoma at the time of vaginal hysterectomy is thought to be less than 1 % [20,21]. Women undergoing a uterine preservation procedure need to be warned of potential uterine and cervical cancer and need to continue with cervical screening.…”
Section: Subsequent Malignancymentioning
confidence: 99%
“…They also found three other cases of uterine premalignant conditions and five cases of CIN in their series of 640 women over nine years. 8 In present study population nine specimens obtained following hysterectomy for POP (as a part of Ward Mayo's procedure) had cervical CIS lesion, which would have required treatment later on. Preoperative for all of these women Pap smear was obtained, though it was the first Pap smear for most of them in their life time.…”
Section: Discussionmentioning
confidence: 86%